Early Life of an Accidental Actor: Before Nayak Raj Razzak - Haque , Muhammed Shahriar (EAST WEST JOURNAL OF HUMANITIES, 2017)
To Bangladeshis, Razzak or Nayak Raj Razzak is the glamorous film star who is pride of this nation. His fans may know all of his characters, memorized each song, cherish every single of his romantic scenes, and kept track of his achievements and accolades acquired over a lifetime. However, how many are aware of the trials, tribulations, and numerous hardship he had to overcome in the early part of his career to taste that success? Nayak Raj Razzak before attaining the iconic status was merely Abdur Razzak. That is why, whenever he is documented by the mass media, he constantly reminds us of his past and the struggles he went through. The background of Razzak’s early life helps us to comprehend how he honed his talent while performing in natok (stage drama/play) for various clubs, theatre groups, and PTV (Pakistan Television), acquired theoretical/practical knowledge of being in front and behind the camera, and became a thespian even before finding success on the silver screen. This paper documents the early life of Abdur Razzak before he became a cinematic legend.